A photoelectric degradation dual-electrode system and its application in degradation of tetracycline hydrochloride wastewater
Through the photoelectric degradation dual electrode system, the synergistic effect of Mo/ZnO/NiF photocatalytic anode and ZnFe2O4/GO/CC catalytic electrode film is solved, and the problem of low degradation efficiency in tetracycline hydrochloride wastewater is achieved, and high-efficiency and low-cost pollutants are achieved handling, with good environmental compatibility and sustainability.
Patent Information
- Application Number
- CN202310041021.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-11
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-01-11
AI Technical Summary
The prior art has low degradation efficiency, high cost and prone to secondary pollution in removing tetracycline hydrochloride wastewater, making it difficult to effectively deal with difficult-to-degrade tetracycline antibiotic pollution.
Using a photoelectric degradation dual electrode system, using Mo/ZnO/NiF photocatalytic anode sheet and ZnFe2O4/GO/CC catalytic electrode film, photogenerating holes and strong oxidizing free radicals are generated through light irradiation, and synergistically degrading tetracycline hydrochloride, achieving no need for Highly efficient degradation of additional power supplies.
It realizes efficient degradation of tetracycline hydrochloride wastewater, reduces treatment costs, has good environmental compatibility and simplicity of operation, and can mineralize tetracycline antibiotics into CO2 and H2O under mild conditions, improving redox performance and degradation efficiency.
Smart Images

Figure CN116040753B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a photoelectric degradation double electrode system and application thereof in degrading tetracycline hydrochloride wastewater, belonging to the technical field of organic polluted wastewater purification and wastewater resource utilization. Background Art
[0002] In recent years, tetracycline antibiotics have been widely used in the fields of medicine, animal husbandry and aquaculture, among which tetracycline hydrochloride (TC-HCl) is one of the most widely used veterinary and human antibiotics. Due to irrational use, TC-HCl tends to accumulate excessively in the environment, which is usually associated with wastewater generation and sewage discharge. As a result, TC-HCl will remain in soil and aquatic ecosystems (river water, groundwater), and eventually appear in drinking water. The pollution of the environment by this substance seriously threatens public health and ecological security. TC-HCl is considered to be a persistent pollutant due to its stable chemical structure and difficulty in degradation. The long-term presence of TC-HCl in the environment can lead to the evolution of antibiotic-resistant bacterial colonies and the production of super bacteria. Therefore, it is crucial to quickly and efficiently convert TC-HCl into inactive and non-toxic byproducts.
[0003] Tetracycline hydrochloride is a difficult-to-degrade organic pollutant. Currently, the main methods for removing tetracycline hydrochloride are adsorption, microbial degradation, electrolysis, advanced oxidation and photocatalysis. These processes generally have problems such as low degradation efficiency, high cost and easy to cause secondary pollution. Summary of the invention
[0004] In order to solve the above technical problems, the present invention proposes a photoelectric degradation dual-electrode system and its application in the degradation of tetracycline hydrochloride wastewater, which does not require additional power supply. Through the action of light, photogenerated holes and SO 4 · - The organic pollutant TC-HCl is degraded under the action of strong oxidizing free radicals. The method for degrading tetracycline hydrochloride wastewater provided by the invention is easy to control, has good environmental compatibility, is simple to operate, and has low cost, so that the difficult-to-degrade TC-HCl wastewater is effectively treated.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention:
[0007] A photoelectric degradation dual-electrode system, the anode is a Mo / ZnO / NiF photocatalytic anode sheet, the cathode is a ZnFe 2 O 4 / GO / CC catalytic electrode membrane assembly, connecting the positive and negative electrodes through wires and externally connected to resistors.
[0008] Furthermore, the Mo / ZnO / NiF photocatalytic anode sheet is connected and fixed by titanium wire, and the Mo / ZnO / NiF photocatalytic anode sheet is prepared with nickel foam as the substrate and Mo / ZnO as the catalyst, wherein the Mo / ZnO catalyst is (NH 4 ) 6 Mo 7 O 24 ·4H 2 O、Zn(Ac) 2 ·2H 2 O、(CH 2 OH) 2 and C 2 H 5 OH prepared.
[0009] Furthermore, the method for preparing the Mo / ZnO / NiF photocatalytic anode sheet comprises the following steps:
[0010] Zn(Ac) 2 ·2H 2 O and (NH 4 ) 6 Mo 7 O 24 ·4H 2 O is added into a mixed solvent of ethanol and ethylene glycol, and magnetic stirring is performed to obtain a blended solvent; the foamed nickel is soaked in ethanol and dried; the dried foamed nickel is added into the blended solvent, and hydrothermally synthesized at 180° C. for 10 h, and after natural cooling, the foamed nickel is taken out and washed with ethanol, and then placed in an oven for heat treatment at 200° C. for 5 h to obtain the Mo / ZnO / NiF photocatalytic anode sheet.
[0011] Furthermore, the Zn(Ac) 2 ·2H 2 O and (NH 4 ) 6 Mo 7 O 24 ·4H 2 The molar ratio of Zn to Mo elements in O is 10:1.
[0012] Furthermore, the ZnFe 2 O 4 / GO / CC catalytic electrode membrane assembly is ZnFe 2 O 4 / GO / CC catalytic electrode membrane is fixed on the membrane assembly, the ZnFe 2 O 4 / GO / CC catalytic electrode membrane is based on ZnFe 2 O 4It is prepared by using / GO as catalyst material, DMF as organic solvent, PVDF as binder, PVP as pore-forming agent and carbon fiber cloth as substrate material.
[0013] Furthermore, the ZnFe 2 O 4 The preparation method of the / GO / CC catalytic electrode film comprises the following steps:
[0014] ZnFe 2 O 4 The ZnFe / GO catalyst was placed in DMF, PVDF and PVP were added, and magnetic stirring was performed for 5 hours to form a casting solution. The casting solution was scraped on a carbon fiber cloth and transferred to clean water. The phase was inverted for 24 hours and dried to obtain the ZnFe 2 O 4 / GO / CC catalytic electrode membrane.
[0015] Furthermore, the ZnFe 2 O 4 / GO catalyst is through Zn(Ac) 2 ·2H 2 O.Fe(NO) 3 9H 2 O,GO and C 2 H 5 OH prepared.
[0016] Furthermore, the ZnFe 2 O 4 The preparation method of / GO catalyst comprises the following steps: Zn(Ac) 2 ·2H 2 O and Fe(NO) 3 9H 2 O was added to ethanol and magnetically stirred to obtain a mixed solution A; GO was added to a mixed solution of DMF and ethanol in a volume ratio of 1:1, and mixed solution B was obtained by ultrasonication; mixed solution A and mixed solution B were mixed, reacted at 180°C for 12h, washed with ethanol, centrifuged, dried, ground, calcined at 400°C for 2h, and cooled to obtain the ZnFe 2 O 4 / GO catalyst.
[0017] The second technical solution of the present invention:
[0018] A method for degrading tetracycline hydrochloride in tetracycline hydrochloride wastewater, wherein the tetracycline hydrochloride wastewater is added to a reaction cell of the photoelectric degradation double electrode system, and H 2 SO 4The solution adjusts the pH value of the wastewater, and then PMS is added to the reaction tank and irradiated with visible light to carry out redox reaction to complete the degradation of tetracycline hydrochloride in the tetracycline hydrochloride wastewater.
[0019] Furthermore, 0.5 mol / L H 2 SO 4 The solution adjusts the wastewater pH to 3-4.
[0020] Furthermore, the concentration of the PMS is 0.2 mM.
[0021] Furthermore, the concentration of tetracycline hydrochloride in the tetracycline hydrochloride wastewater is 10-100 mg / L.
[0022] Under visible light irradiation, the Mo / ZnO / NiF photocatalytic anode that can generate photogenerated electrons is used as the power source, and the ZnFe 2 O 4 The Fe on the / GO / CC catalytic cathode film activates PMS, thereby promoting the production of strong oxidative free radicals SO 4 · - The photogenerated holes generated by the Mo / ZnO / NiF photocatalytic anode also have strong oxidizing properties, which can open or break the tetracycline hydrochloride molecules, thereby achieving the degradation of tetracycline hydrochloride. 2 O 4 The / GO / CC catalytic electrode membrane as a cathode membrane not only activates PMS, but also has a certain filtering effect.
[0023] The photoelectric degradation dual-electrode system of the present invention does not require an additional power supply. Through the action of light, the photoanode can generate photogenerated electron-hole pairs, and the photogenerated electrons reach the cathode through an external circuit, achieving effective separation of the electron-hole pairs while promoting the cathode film Fe 2+ with Fe 3+ cycle, the photogenerated holes have strong oxidizing properties, and the Fe ions loaded on the cathode film can activate PMS to produce SO 4 · - , in the photogenerated holes and SO 4 · - The organic pollutant TC-HCl is degraded under the action of strong oxidizing free radicals.
[0024] The present invention uses photocatalytic degradation technology to degrade tetracycline hydrochloride wastewater, which is easy to control, has good environmental compatibility, is easy to automate, is simple to operate, has low cost, and is sustainable. In addition, solar energy is used to degrade TC-HCl into CO under mild conditions. 2 and H 2O. The present invention introduces photogenerated electrons generated by the photocatalytic anode to provide the required electrical energy for activating PMS, and simultaneously introduces sunlight as energy to catalyze the degradation of pollutants, which can not only improve the redox performance and degradation efficiency, but also save energy consumption and reduce costs.
[0025] The photoelectric degradation dual-electrode system of the present invention can realize the efficient removal of TC-HCl in TC-HCl antibiotic wastewater, so that the difficult-to-degrade TC-HCl wastewater can be effectively treated.
[0026] The present invention discloses the following technical effects:
[0027] (1) The Mo / ZnO / NiF photocatalytic anode sheet of the photoelectric degradation dual-electrode system of the present invention has a large specific surface area, many active sites, low cost, and is easy to prepare; the Mo / ZnO / NiF photocatalytic anode sheet has sustainable utilization and can be repeatedly used to achieve efficient degradation of pollutants.
[0028] (2) Compared with the traditional method for degrading organic polluted wastewater, the method of degrading tetracycline hydrochloride in tetracycline hydrochloride wastewater of the present invention utilizes a photocatalyst to cooperate with a PMS system under sunlight to achieve effective separation of electron-hole pairs while promoting the degradation of cathode film Fe 2+ with Fe 3+ cycle, the photogenerated holes have strong oxidizing properties, and the Fe ions loaded on the cathode film can activate PMS to produce SO 4 · - , in the photogenerated holes and SO 4 ·-, etc., to open the ring and break the organic pollutant TC-HCl. In addition, the present invention performs visible light irradiation outside the reaction pool, which improves the redox performance of the reaction, significantly improves the activation performance of PMS, and is beneficial to SO 4 -The production of strong oxidative free radicals.
[0029] (3) The photoelectric degradation dual-electrode system of the present invention effectively improves the degradation efficiency of TC-HCl in wastewater and effectively recycles and utilizes TC-HCl wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0031] Figure 1 The cyclic voltammograms of the photocatalytic anode sheets prepared in Example 1 and Comparative Examples 1-3;
[0032] Figure 2 The transient photocurrent response curves of the photocatalytic anode sheets prepared in Example 1 and Comparative Examples 1-3;
[0033] Figure 3 This is a treatment performance diagram for the degradation of TC-HCl in Example 1, where the left ordinate represents the degradation rate and the right ordinate represents the removal efficiency. DETAILED DESCRIPTION
[0034] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0035] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0036] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0037] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0038] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0039] The present invention proposes a photoelectric degradation dual-electrode system, wherein the anode is a Mo / ZnO / NiF photocatalytic anode sheet and the cathode is a ZnFe 2 O 4 / GO / CC catalytic electrode membrane assembly, connecting the positive and negative electrodes through wires and externally connected to resistors.
[0040] Furthermore, the Mo / ZnO / NiF photocatalytic anode sheet is connected and fixed by titanium wire. The Mo / ZnO / NiF photocatalytic anode sheet is prepared with nickel foam as the substrate and Mo / ZnO as the catalyst. The Mo / ZnO catalyst is composed of (NH 4 ) 6 Mo 7 O 24 ·4H 2 O、Zn(Ac) 2 ·2H 2 O、(CH 2 OH) 2 and C 2 H 5 OH prepared.
[0041] In an embodiment of the present invention, the method for preparing the Mo / ZnO / NiF photocatalytic anode sheet comprises the following steps:
[0042] 2.2 g Zn(Ac) 2 ·2H 2 O and 0.177 g (NH 4 ) 6 Mo 7 O 24 ·4H 2 O is added into 40 ml of a mixed solvent of ethanol and ethylene glycol in a volume ratio of 3:1, and magnetic stirring is performed for 5 hours to obtain a blended solvent; the foamed nickel is soaked in ethanol for 1 hour and dried at 60° C.; the dried foamed nickel is placed in a 100 ml polytetrafluoroethylene liner, and the fully dissolved blended solvent is added, and hydrothermal synthesis is performed in a high-pressure reactor at 180° C. for 10 hours, and after natural cooling, the foamed nickel is taken out and washed with ethanol, and placed in an oven for heat treatment at 200° C. for 5 hours, and after cooling, the Mo / ZnO / NiF photocatalytic anode sheet is obtained.
[0043] In the embodiment of the present invention, the Zn(Ac) 2 ·2H 2 O and (NH 4 ) 6 Mo 7 O 24 ·4H 2 The molar ratio of Zn to Mo elements in O is 10:1.
[0044] Furthermore, the ZnFe 2 O 4 / GO / CC catalytic electrode membrane assembly is ZnFe 2 O 4 / GO / CC catalytic electrode membrane is fixed on the membrane assembly, the ZnFe 2 O 4 / GO / CC catalytic electrode membrane is based on ZnFe 2 O 4 It is prepared by using / GO as catalyst material, DMF as organic solvent, PVDF as binder, PVP as pore-forming agent and carbon fiber cloth as substrate material.
[0045] In the embodiment of the present invention, the ZnFe 2 O 4 The preparation method of the / GO / CC catalytic electrode film comprises the following steps:
[0046] 0.5g ZnFe 2 O 4 The ZnFe / GO catalyst was placed in 8 g of DMF, 1 g of PVDF and 0.5 g of PVP were added, and magnetic stirring was performed for 5 h to form a casting solution. The casting solution was evenly scraped on the carbon fiber cloth, and quickly transferred to clean water for phase conversion for 24 h, and dried to obtain the ZnFe 2 O 4 / GO / CC catalytic electrode membrane.
[0047] Furthermore, the ZnFe 2 O 4 / GO catalyst is through Zn(Ac) 2 ·2H 2 O.Fe(NO) 3 9H 2 O,GO and C 2 H 5 OH prepared.
[0048] In the embodiment of the present invention, the ZnFe 2 O 4 The preparation method of / GO catalyst comprises the following steps: 2.75g Zn(Ac) 2 ·2H 2 O and 10.1 g Fe(NO) 3 9H 2 O was added to 100 ml of ethanol and magnetically stirred for 1 hour until the color turned dark brown; 0.5 g of GO was added to 40 ml of DMF and ethanol with a volume ratio of 1:1, and ultrasonicated for 20 minutes; the above two solutions were mixed and placed in a 250 ml polytetrafluoroethylene liner, reacted at 180°C in a high-pressure reactor for 12 hours, washed with ethanol, centrifuged, dried, ground, calcined at 400°C for 2 hours, and cooled to obtain the ZnFe 2 O 4 / GO catalyst.
[0049] The present invention also proposes a method for degrading tetracycline hydrochloride in tetracycline hydrochloride wastewater, wherein the tetracycline hydrochloride wastewater is added into the reaction pool of the photoelectric degradation double electrode system, and H2 SO 4 The solution adjusts the pH value of the wastewater, and then PMS is added to the reaction tank and irradiated with visible light to carry out redox reaction to complete the degradation of tetracycline hydrochloride in the tetracycline hydrochloride wastewater. Under visible light irradiation, the Mo / ZnO / NiF photocatalytic anode sheet that can generate photogenerated electrons is used as the power source, and the ZnFe 2 O 4 The Fe on the / GO / CC catalytic cathode film activates PMS, thereby promoting the production of strong oxidative free radicals SO 4 · - The photogenerated holes generated by the Mo / ZnO / NiF photocatalytic anode also have strong oxidizing properties, which can open or break the tetracycline hydrochloride molecules, thereby achieving the degradation of tetracycline hydrochloride. 2 O 4 The / GO / CC catalytic electrode membrane as a cathode membrane not only activates PMS, but also has a certain filtering effect.
[0050] In the present embodiment, 0.5 mol / L H 2 SO 4 The solution adjusts the pH value of the solution to 3-4, preferably to 3. When the pH value is 3, the degradation rate of tetracycline hydrochloride within 30 minutes can be as high as 98.6%. When the pH value exceeds the range of 3-4, the degradation rate is lower than this.
[0051] In the embodiment of the present invention, the concentration of PMS is 0.2 mM.
[0052] In an embodiment of the present invention, the concentration of tetracycline hydrochloride in the tetracycline hydrochloride wastewater is 10-100 mg / L.
[0053] All raw materials used in the examples of the present invention are commercially available.
[0054] The technical solution of the present invention is further illustrated by the following embodiments.
[0055] Example 1
[0056] (1) Preparation of Mo / ZnO / NiF photocatalytic anode
[0057] 2.2 g Zn(Ac) 2 ·2H 2 O and 0.177 g (NH 4 ) 6 Mo 7 O 24 ·4H 2O (the molar ratio of Zn to Mo elements is 10:1) is added to 40 ml of a mixed solvent of ethanol and ethylene glycol in a volume ratio of 3:1, and magnetic stirring is performed for 5 hours to obtain a blended solvent; the foamed nickel is soaked in ethanol for 1 hour and dried at 60°C; the dried foamed nickel is placed in a 100 ml polytetrafluoroethylene liner, and the fully dissolved blended solvent is added, and a high-pressure reactor is hydrothermally synthesized at 180°C for 10 hours, and after natural cooling, the foamed nickel is taken out and washed with ethanol, and placed in an oven for heat treatment at 200°C for 5 hours, and after cooling, a Mo / ZnO / NiF photocatalytic anode sheet is obtained;
[0058] (2) ZnFe 2 O 4 Preparation of / GO / CC catalytic electrode membrane
[0059] 2.75 g Zn(Ac) 2 ·2H 2 O and 10.1 g Fe(NO) 3 9H 2 O was added to 100 ml of ethanol and magnetically stirred for 1 h until the color turned dark brown; 0.5 g of GO was added to 40 ml of DMF and ethanol in a volume ratio of 1:1 and ultrasonicated for 20 min; the above two solutions were mixed and placed in a 250 ml polytetrafluoroethylene liner, reacted at 180 ° C for 12 h in an autoclave, washed with ethanol, centrifuged, dried, ground, calcined at 400 ° C for 2 h, and cooled to obtain ZnFe 2 O 4 / GO catalyst;
[0060] 0.5g ZnFe 2 O 4 The / GO catalyst was placed in 8g DMF, 1g PVDF and 0.5g PVP were added, and magnetic stirring was performed for 5h to form a casting solution. The casting solution was evenly scraped on the carbon fiber cloth, and quickly transferred to clean water for phase conversion for 24h, and dried to obtain ZnFe 2 O 4 / GO / CC catalytic electrode membrane;
[0061] (3) Construction of dual-electrode system for photoelectrochemical degradation
[0062] The Mo / ZnO / NiF photocatalytic anode sheet was fixed by titanium wire. 2 O 4 The / GO / CC catalytic electrode membrane is fixed on the membrane assembly as the cathode, and the positive and negative electrodes are connected by wires and an external resistor;
[0063] (4) Photoelectric degradation of tetracycline hydrochloride wastewater using a dual-electrode system
[0064] The TC-HCl wastewater was added to the reaction cell of the photoelectric degradation double electrode system, and 0.5 mol / L H 2 SO 4 The pH value of the wastewater was adjusted to 3, the TC-HCl wastewater covered the Mo / ZnO / NiF photocatalytic anode and cathode membrane components, a PMS concentration of 0.2 mM was added, and a xenon lamp (PL-X300D / PL-X300DUV) was used to simulate sunlight outside the reaction tank for irradiation. The power was 300 W, the working current was 17.5 A, and the luminescence spectrum range was 200 nm-2500 nm, which promoted the redox reaction and completed the degradation of tetracycline hydrochloride in the tetracycline hydrochloride wastewater.
[0065] Comparative Example 1
[0066] (1) Preparation of Mo / ZnO / NiF photocatalytic anode
[0067] Same as Example 1, except that 2.2 g Zn(Ac) 2 ·2H 2 O and 0.220 g (NH 4 ) 6 Mo 7 O 24 ·4H 2 O is added to a mixed solvent of ethanol and ethylene glycol, that is, the molar ratio of Zn to Mo elements is 8:1;
[0068] (2) ZnFe 2 O 4 Preparation of / GO / CC catalytic electrode membrane
[0069] Same as Example 1;
[0070] (3) Construction of dual-electrode system for photoelectrochemical degradation
[0071] Same as Example 1;
[0072] (4) Photoelectric degradation of tetracycline hydrochloride wastewater using a dual-electrode system
[0073] Same as Example 1.
[0074] Comparative Example 2
[0075] (1) Preparation of Mo / ZnO / NiF photocatalytic anode
[0076] Same as Example 1, except that 2.2 g Zn(Ac) 2 ·2H 2 O and 0.147 g (NH 4 ) 6 Mo 7 O 24 ·4H2 O is added into a mixed solvent of ethanol and ethylene glycol, that is, the molar ratio of Zn to Mo elements is 12:1;
[0077] (2) ZnFe 2 O 4 Preparation of / GO / CC catalytic electrode membrane
[0078] Same as Example 1;
[0079] (3) Construction of dual-electrode system for photoelectrochemical degradation
[0080] Same as Example 1;
[0081] (4) Photoelectric degradation of tetracycline hydrochloride wastewater using a dual-electrode system
[0082] Same as Example 1.
[0083] Comparative Example 3
[0084] (1) Preparation of ZnO / NiF photocatalytic anode
[0085] Same as Example 1, except that (NH 4 ) 6 Mo 7 O 24 ·4H 2 The addition of O;
[0086] (2) ZnFe 2 O 4 Preparation of / GO / CC catalytic electrode membrane
[0087] Same as Example 1;
[0088] (3) Construction of dual-electrode system for photoelectrochemical degradation
[0089] Same as Example 1;
[0090] (4) Photoelectric degradation of tetracycline hydrochloride wastewater using a dual-electrode system
[0091] Same as Example 1.
[0092] Performance Test 1
[0093] The oxidizability of the photocatalytic anode sheets prepared in Example 1 and Comparative Examples 1-3 was tested by cyclic voltammetry at a scan rate of 0.01 V / s in a 1 mol / L Na solution with a pH value of 2.85. 2 SO 4 The cyclic voltammetry of the catalytic anodes with different Mo doping amounts was carried out in the solution. Figure 1(The horizontal axis in the figure represents voltage, unit v, the vertical axis represents current, unit A, the scanning rate is 0.01V / s, in 1mol / L Na with a pH value of 2.85 2 SO 4 Scanning cyclic voltammogram in solution). Figure 1 It can be seen that the cyclic voltammetry curve of the catalytic anode prepared in Example 1 (the ratio of the amount of Zn and Mo elements is 10:1) has an obvious oxidation peak compared with that of Comparative Example 1 (the ratio of the amount of Zn and Mo elements is 8:1), Comparative Example 2 (the ratio of the amount of Zn and Mo elements is 12:1) and Comparative Example 3 (no Mo element added), indicating that the catalytic anode with a ratio of Zn and Mo elements of 10:1 has a significant promoting effect on the oxidation reaction.
[0094] Performance Test 2
[0095] The transient photocurrent response of the photocatalytic anode sheets prepared in Example 1 and Comparative Examples 1-3 was tested. The separation and migration of charges inside the photocatalyst can be reflected by the photocurrent response. The transient photocurrent measurement results of the switching cycle of 30s under xenon lamp irradiation were shown in the electrochemical workstation. Figure 2 (The horizontal axis in the figure represents time, unit s, and the vertical axis represents current density, unit A / cm 2 ).Depend on Figure 2 It can be seen that the high conductivity and stable photosensitivity of the Mo / ZnO / NiF photocatalytic anode sheet prepared in Example 1 (the molar ratio of Zn to Mo is 10:1) can reduce the recombination of electrons and holes, and the photocurrent response is much higher than that of Comparative Examples 1-3.
[0096] Performance Test 3
[0097] The photoelectric degradation dual-electrode system constructed in Example 1 was tested for its effect on the degradation of tetracycline hydrochloride wastewater. The concentrations of TC-HCl in the TC-HCl wastewater in step (4) of Example 1 were adjusted to 10 mg / L, 20 mg / L, 50 mg / L and 100 mg / L, respectively, and the performance of the system in treating TC-HCl was tested. The results are shown in FIG. Figure 3 (The horizontal axis in the figure represents time, in minutes; the vertical axis on the left represents the degradation rate, and the vertical axis on the right represents the removal efficiency, that is, the blue line represents the removal efficiency, and the green line represents the degradation rate). Figure 3 It can be seen that the photoelectric degradation dual-electrode system of Example 1 of the present invention can effectively remove TC-HCl and achieve effective purification of TC-HCl wastewater.
[0098] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A photoelectric degradation dual-electrode system, characterized in that: The anode is a Mo / ZnO / NiF photocatalytic anode sheet, and the cathode is a ZnFe2O4 / GO / CC catalytic electrode membrane assembly, which is connected to the positive and negative electrodes by wires and an external resistor; The method for preparing the Mo / ZnO / NiF photocatalytic anode sheet comprises the following steps: Zn(Ac)2·2H2O and (NH4)6Mo7O 24 4H2O is added to a mixed solvent of ethanol and ethylene glycol, and magnetic stirring is performed to obtain a mixed solvent; the foamed nickel is soaked in ethanol and dried; the dried foamed nickel is added to the mixed solvent, and hydrothermally synthesized at 180°C for 10 hours, and after natural cooling, the foamed nickel is taken out and washed with ethanol, and then placed in an oven for heat treatment at 200°C for 5 hours to obtain the Mo / ZnO / NiF photocatalytic anode sheet; The Zn(Ac)2·2H2O and (NH4)6Mo7O 24 The molar ratio of Zn to Mo in 4H2O is 10:1; The ZnFe2O4 / GO / CC catalytic electrode membrane assembly is obtained by fixing the ZnFe2O4 / GO / CC catalytic electrode membrane on a membrane assembly. The ZnFe2O4 / GO / CC catalytic electrode membrane is prepared using ZnFe2O4 / GO as a catalyst material, DMF as an organic solvent, PVDF as a binder, PVP as a pore-forming agent, and carbon fiber cloth as a base material.
2. The photoelectric degradation dual-electrode system according to claim 1, characterized in that: The Mo / ZnO / NiF photocatalytic anode sheet is connected and fixed by titanium wire.
3. The photoelectric degradation dual-electrode system according to claim 1, characterized in that: The ZnFe2O4 / GO catalyst is prepared by Zn(Ac)2·2H2O, Fe(NO)3·9H2O, GO and C2H5OH.
4. A method for degrading tetracycline hydrochloride in tetracycline hydrochloride wastewater, characterized in that: The tetracycline hydrochloride wastewater is added to the reaction cell of the photoelectric degradation dual-electrode system according to any one of claims 1 to 3, the pH value of the wastewater is adjusted with H2SO4 solution, and then PMS is added to the reaction cell, and irradiated with visible light to complete the degradation of tetracycline hydrochloride in the tetracycline hydrochloride wastewater.
5. The method for degrading tetracycline hydrochloride in tetracycline hydrochloride wastewater according to claim 4, characterized in that: Use 0.5 mol / L H2SO4 solution to adjust the pH value of the wastewater to 3-4.
6. The method for degrading tetracycline hydrochloride in tetracycline hydrochloride wastewater according to claim 4, characterized in that: The concentration of the PMS was 0.2 mM.
7. The method for degrading tetracycline hydrochloride in tetracycline hydrochloride wastewater according to claim 4, characterized in that: The concentration of tetracycline hydrochloride in the tetracycline hydrochloride wastewater is 10-100 mg / L.
Citation Information
Patent Citations
Foamed nickel-loaded zinc titanate photocatalytic material and preparation method thereof
CN109482190A